Imperative Sentence in Papuan’s Prose entitled Asal Mula Kerang dan Sungai Kohoin. - Insum Insum Malawat (Universitas Negeri Gorontalo, 2022)
Abstract The title of this research is Imperative Sentence in Papuan’s Prose entitled Asal Mula Kerang dan Sungai Kohoin. It is a literature pragmatic study. Literature Pragmatic Study aims at describing imperative sentences and their practical function to the reader. It uses a qualitative content analysis approach. The technic used to collect the data is listening and writing. Based on the result of the research, it is concluded that AMK and SK consist of 5 imperative sentences. Those are normal, allowing, forbidden, request, and conditional imperative sentences. These imperative sentences are dominated by forbidden affirmative sentences. Normal, allowing, and requesting imperative sentences consist of begging something from others that aim at balancing nature and human life. Forbidden and conditional imperative sentences deliver a massage of obedience packing it in the taboo issue. All of the imperative sentences in both narratives treat nature as a friend of human beings, not an enemy. The result of this research can be used as one of the ways to study kinds of sentences at school.